PEMANFAATAN KULIT DAN BONGGOL PISANG UNTUK BAHAN BAKU MAKANAN RINGAN DI MAJELIS TAKLIM AN NUR CILEUNYI KABUPATEN BANDUNG - Amalia, Vina; Rosahdi, Tina Dewi; Sudiarti, Tety (Al-Khidmat : Jurnal Ilmiah Pengabdian Kepada masyarakat, 2019)
Banana is a favorite fruit of the Indonesian people. So far, only the fruit is consumed, while the peel, hump and others are useless and become waste. The banana peel and banana humps contain high nutritional value. So that it has the potential to be processed as a food product, such as â€œsaleâ€ of banana peels, abon and banana hump jerky. This product can be an added income for womanâ€™s, the members of the Taklim (MT) assembly of An Nur. MT consists of womanâ€™s from various professional backgrounds. Most of them are ordinary housewives who are also agent of Posyandu RW 03 Cileunyi Kulon Village, Kec. Cileunyi Kab. Bandung. Some of them are teachers and entrepreneurs. Training on making food made from banana humps and peel was carried out for two months. Consisting of counseling on nutritional content, the practice of making â€œSaleâ€, shredded meat and beef jerky, and marketing strategies. The obstacle faced is the limitation of banana humps, because banana only found when bananas are harvested. While the processing of banana peels produces products that have less attractive colors because of the browning process that is common in processing bananas so that dyes are needed. Marketing using online media is not suitable for members of MT An Nur, where only a few members have social media and smart phones. In the future, this skill is expected to be the provision of mothers to improve their nutritional status and family economy and can be disseminated through their own MT programs and posyandu programs at the RW, village and sub-district levels.